Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo–West Pacific, with comments on the distribution of T. eschmeyeri - Motomura, Hiroyuki; Last, Peter R.; Yearsley, Gordon K. (Zootaxa, 2007)
Two new species of the scorpionfish genus Trachyscorpia are described on the basis of 20 and 7 specimens collected from Australasia at depths of 731–1020 m and the southwestern Indian Ocean at depths of 620–1080 m respectively. The two new species, classified into the subgenus Mesoscorpia, are distinguished from the only other member of the subgenus, T. (M.) eschmeyeri, by the following characters: the tympanic spines absent (vs. usually present in the latter), the upper-jaw lip well developed, covering the premaxillary tooth band laterally (vs. lip poorly developed, the premaxillary teeth exposed laterally), scales absent on the lateral surface of the maxilla (vs. scales present), and 4 blackish saddles on the body in preserved specimens (vs. no blackish saddles). Trachyscorpia (M.) carnomagula sp. nov. differs from T. (M.) longipedicula sp. nov. in having 57–63 scale rows in longitudinal series (vs. 50–53 in the latter). They are also distinguished by several morphometric characters, including lengths of pelvic-fin spine and soft ray, and first anal-fin spine. The subgenus Mesoscorpia is redefined. A key to the species of Trachyscorpia and comments on distribution of T. (M.) eschmeyeri are also provided.